Palladium-Zeolite nanofiber as an effective recyclable catalyst membrane for water treatment. (15th September 2016) - Choi, Jungsu; Chan, Sophia; Yip, Garriott; Joo, Hyunjong; Yang, Heejae; Ko, Frank K.
Abstract: Zeolite is an exciting natural material due to its unique capability of ammonium nitrogen (NH3 N) adsorption in water. In this study, multifunctional hybrid composites of zeolite/palladium (Ze/Pd) on polymer nanofiber membranes were fabricated and explored for sustainable contaminant removal. SEM and XRD demonstrated that zeolite and palladium nanoparticles were uniformly distributed and deposited on the nanofibers. NH3 N recovery rate was increased from 23 to 92% when palladium coated zeolite was embedded on the nanofiber. Multifunctional nanofibers of Ze/Pd membranes were able to adsorb NH3 N on the zeolites placed on the surface of fibers and palladium catalysts were capable of selective oxidation of NH3 N to N2 gas. The cycling of NH3 N adsorption-oxidation, high flux, hydrophilicity, and flexibility of the membrane makes it a strong candidate for water treatment. Graphical abstract: Highlights: Zeolite and palladium nanoparticles were uniformly deposited on the nanofibers. Palladium catalysts were capable of selective oxidation of NH3 N to N2 gas. Multifunctional nanofibrous membranes were able to absorb and remove NH3 N. Ze/Pd nanofiber membrane can be recycled and reused for NH3 N removal. Recovery rate of Ze/Pd membranes functions were shown to be 92.2% at 250 °C.